Les politiques de l'emploi en Europe et aux Éats-Unis - Bellemare, Diane (Relations industrielles / Industrial Relations, 1999)
The article reviews the book, "Les politiques de l'emploi en Europe et aux Éats-Unis," edited by Jean-Claude Barbier and Jérôme Gautié.
Keywords: Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Employment; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z